1997
DOI: 10.1046/j.1537-2995.1997.37697335160.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of screening for hepatitis C virus in children with malignant disease and who undergo bone marrow transplantation

Abstract: A considerable number of children with primary malignant disease who received multiple blood transfusions became infected by HCV before HCV screening was used. Patients who underwent BMT were at high risk for HCV infection. Screening with a second-generation HCV antibody test has proven to be remarkably beneficial in preventing HCV infection in these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Recent publications have suggested that children infected after vertical infection have a higher spontaneous clearance than adults. [8][9][10] These results are similar to the horizontal infection of young children after HCV positive blood transfusion. The spontaneous clearance rate in these patients was between 28 and 55%.…”
Section: Discussionsupporting
confidence: 78%
“…Recent publications have suggested that children infected after vertical infection have a higher spontaneous clearance than adults. [8][9][10] These results are similar to the horizontal infection of young children after HCV positive blood transfusion. The spontaneous clearance rate in these patients was between 28 and 55%.…”
Section: Discussionsupporting
confidence: 78%
“…5 Other papers analyze the results of serological tests in BMT and immunocompromised patients. 10,15,[17][18][19][20][21][22][23] Toma´s et al 23 found in a retrospective study of 61 BMT patients who had hepatic pathology, 29 patients with chronic hepatitis C of whom seven constantly tested anti-HCV negative but PCR positive. The Seattle group recommends hepatitis C testing, including viral RNA analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 22 responding members, five reported on 37 cases of patients with chronic HCV infection who were treated with peginterferon and ribavirin (Table 1) and the remaining 16 members reported that they had no such patient. Twenty-two of the 37 patients had undergone a blood transfusion between 1983 and 1989, before the introduction of a screening test for anti-HCV antibodies in Japan [18]. Criteria for inclusion in the study were chronic HCV infection and determination of genotype, 30 years of age or younger, and normal values for hemoglobin, platelets, white blood cells, bilirubin, glucose, and serum creatinine.…”
Section: Methodsmentioning
confidence: 99%